2015
DOI: 10.1097/sap.0b013e31828d9983
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Salvaging Impending Flap Congestion in Breast Reconstruction by Venous Supercharging of the Cephalic Vein

Abstract: Autologous flap breast reconstruction is an established technique that carries a risk of vascular failure. We evaluated the safety of salvaging impending venous congestion by using the cephalic vein for supercharging autologous abdominal flaps. Our main outcome measures were flap survival, triggering or impairing lymphedema as measured by the physician or reported by the patient, and scar severity as measured by the Vancouver scar scale. We were able to save 100% of the flaps, but could not find any statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
1
12
0
2
Order By: Relevance
“…Other common strategies include the anastomosis of the SIEV to a second internal mammary vein, to an internal mammary perforator, or end-to-side to one of the DIEVs of the flap. [10,25,26] Less popular options include the anastomosis of the SIEV to the thoracoacromial vein, to the contralateral intermammary vein (which may need a vein graft), or to the toracodorsal vein (which may prevent the use of a latissimus dorsi as a rescue surgery in case the DIEP flap fails), among others. Notwithstanding, carrying out a second venous anastomosis is timeconsuming, which represents the main drawback of this procedure, taking between 30 to 90 min.…”
Section: Taking Into Account the Redirection Of The Venousmentioning
confidence: 99%
See 2 more Smart Citations
“…Other common strategies include the anastomosis of the SIEV to a second internal mammary vein, to an internal mammary perforator, or end-to-side to one of the DIEVs of the flap. [10,25,26] Less popular options include the anastomosis of the SIEV to the thoracoacromial vein, to the contralateral intermammary vein (which may need a vein graft), or to the toracodorsal vein (which may prevent the use of a latissimus dorsi as a rescue surgery in case the DIEP flap fails), among others. Notwithstanding, carrying out a second venous anastomosis is timeconsuming, which represents the main drawback of this procedure, taking between 30 to 90 min.…”
Section: Taking Into Account the Redirection Of The Venousmentioning
confidence: 99%
“…However, the overall risk appears to be reasonably low, being able to consider the harvest of the cephalic vein a safe option. [25] The systematic venous supercharging has been advocated to prevent the potential drainage insufficiency, after significant results experiencing less congestion. [26] However, a recent meta-analysis has failed to demonstrate the efficacy of the SIEV supercharging to reduce the flap-related complication rate.…”
Section: Taking Into Account the Redirection Of The Venousmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have described superdrainage to the CV for breast reconstruction (Audolfsson et al, ; Barnett et al, ; Enajat et al, ; Landin et al, ; Mehrara et al, ; Powell et al, ). Morteza et al previously reported that the ratio of anastomoses, which include superdrainage, was ~50%.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the serratus anterior muscle branch of the thoracodorsal vein (SA) is anastomosed to the drainage vein (recipient vein), although blood vessel anastomosis can occasionally be difficult. Some reports have described a method using the cephalic vein (CV) for superdrainage (Audolfsson et al, ; Barnett, Carlisle, & Gianoutsos, ; Chang, Fearmonti, Chang, & Butler, ; Enajat, Rozen, Whitaker, Smit, & Acosta, ; Landin et al, ; Mehrara et al, ; Powell, Prousskaia, & Wilson, ). However, the suggestions of superdrainage, and which vein should be used, have been points of debate.…”
Section: Introductionmentioning
confidence: 99%